Examining Students' Reading Habit and Gender Differences behind Students' Academic Writing Achievement - Sari Rahmawati (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2021)
Students’ reading habit and gender differences are believed as two influential factors on students’ academic writing achievement. The purposes of this study were to find out the effect of the two factors on students’ academic writing achievement and to find out the relationship among them. 43 English students of UIN Imam Bonjol Padang in the fourth semester registered in academic year 2020/2021 were involved. Reading habit questionnaire and essay writing test were administered. To analyze the data, simple regression test, multiple regression test, and Pearson’s correlation test were applied. It was revealed that reading habit had no effect on students’ academic writing achievement; they had very weak correlation, whereas gender affected students’ academic writing achievement; they had weak relationship. Moreover, students’ reading habit and gender affected students’ academic writing achievement as many as 10.4 %.